5(4c-1)-5=18c+8

Simple and best practice solution for 5(4c-1)-5=18c+8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(4c-1)-5=18c+8 equation:


Simplifying
5(4c + -1) + -5 = 18c + 8

Reorder the terms:
5(-1 + 4c) + -5 = 18c + 8
(-1 * 5 + 4c * 5) + -5 = 18c + 8
(-5 + 20c) + -5 = 18c + 8

Reorder the terms:
-5 + -5 + 20c = 18c + 8

Combine like terms: -5 + -5 = -10
-10 + 20c = 18c + 8

Reorder the terms:
-10 + 20c = 8 + 18c

Solving
-10 + 20c = 8 + 18c

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '-18c' to each side of the equation.
-10 + 20c + -18c = 8 + 18c + -18c

Combine like terms: 20c + -18c = 2c
-10 + 2c = 8 + 18c + -18c

Combine like terms: 18c + -18c = 0
-10 + 2c = 8 + 0
-10 + 2c = 8

Add '10' to each side of the equation.
-10 + 10 + 2c = 8 + 10

Combine like terms: -10 + 10 = 0
0 + 2c = 8 + 10
2c = 8 + 10

Combine like terms: 8 + 10 = 18
2c = 18

Divide each side by '2'.
c = 9

Simplifying
c = 9

See similar equations:

| 5y+4a=13 | | 20+14z=11z-20-8 | | -185=-32+17r | | 4s+1k=3r | | 13n=69 | | 11x+24=-2 | | 8z+7=-5z-57 | | 8-n=-4+2(4-n) | | 5.25q-2(3q+1.25)=q+1 | | 4s+k=3r | | 9.2s=12.8s-3.96 | | 3y^2=72 | | -20p=-15.58-11.8p | | (9x-5)-(6x-8)= | | 2m+2n+2m+4n+8= | | 7x-5(5x+4)=142 | | 28M+16=4(4M-23) | | 7y^2-49y=0 | | -3=4x+6minusx | | 2n+8+2n+20= | | -n+25+6n+15=-12 | | 7x+5(5+4)=142 | | d(7-x)=4v | | 16+11v=2v-20+6v | | 10x-31+9x-13=127 | | R+300=-214 | | 152-x=138 | | 3(x+y)=8 | | 1.5(4w+1)=2.5w+1 | | -2n-(n-5)=n+1 | | 2x+4x-4=-2x+4 | | (y+2)(y-7)-1=(y+1)(y+3) |

Equations solver categories